Vancomycin-Loaded Silk Fibroin/Calcium Phosphate/Methylcellulose-Based In Situ Thermosensitive Hydrogel: A Potential Function for Bone Regeneration - Premchirakorn Phewchan; Artit Laoruengthana; Pratthana Chomchalao; Supaporn Lamlertthon; Waree Tiyaboonchai (Gels)
This study explores the efficacy of a vancomycin-loaded silk fibroin/calcium phosphate/methylcellulose-based in situ thermosensitive hydrogel (VM-SF/CaP/MC) in promoting the osteogenic differentiation of preosteoblast cells. Three VM-SF/CaP/MC formulations with varying low (L) and high (H) concentrations of silk fibroin (SF) and calcium phosphate (CaP) were prepared: VM-HSF/LCaP/MC, VM-LSF/HCaP/MC, and VM-HSF/HCaP/MC. These hydrogels significantly enhanced MC3T3-E1 cell migration and proliferation in a dose- and time-dependent manner, achieving complete cell migration within 48 h. In addition, they significantly promoted alkaline phosphatase activity, collagen content, and mineralization in MC3T3-E1 cells, indicating their potential for osteogenesis. Among the hydrogel formulations, the VM-HSF/HCaP/MC hydrogel, with high SF and CaP content, demonstrated superior potential in promoting the osteogenic differentiation of MC3T3-E1 cells. It exhibited the highest ALP activity (11.13 ± 0.91 U/mg protein) over 14 days, along with increased collagen content (54.00 ± 1.71 µg/mg protein) and mineralization (15.79 ± 1.48 mM) over 35 days. Therefore, this formulation showed a promising candidate for clinical application in localized bone regeneration, particularly in treating osteomyelitis.